Adherence to Follow-up Recommendations Among Individuals in the Philadelphia Glaucoma Detection and Treatment Project. Issue 8 (August 2017) - Hark, Lisa A.; Leiby, Benjamin E.; Waisbourd, Michael; Myers, Jonathan S.; Fudemberg, Scott J.; Mantravadi, Anand V.; Dai, Yang; Gilligan, John P.; Resende, Arthur F.; Katz, L. Jay
Abstract : Purpose: To evaluate rates of adherence to free follow-up eye exam appointments among participants in the Philadelphia Glaucoma Detection and Treatment Project. Patients and Methods: Ophthalmologists and testing equipment were brought directly to participants at risk for glaucoma at 43 community sites in Philadelphia. Those diagnosed with glaucoma-related pathology were recommended to return for follow-up to be reexamined on site. Rates of adherence and clinical and demographic risk factors for adherence were evaluated. Results: Five hundred thirty-one participants were diagnosed with glaucoma-related conditions and recommended to attend community-based follow-up exams. Follow-up adherence rate was 61.2% (n=325/531). Significant factors associated with greater eye exam appointment adherence, based on our univariable analysis, included final diagnosis of glaucoma (risk ratio [RR]=1.33; 95% confidence interval [CI], 1.13-1.57), male sex (RR=1.19; 95% CI, 1.04-1.36), white race (RR=1.26; 95% CI, 1.08-1.48), age (RR=1.17; 95% CI, 1.00-1.37) recommendation for glaucoma medication (RR=1.52; 95% CI, 1.35-1.71), recommendation for laser peripheral iridotomy (RR=1.18; 95% CI, 1.02-1.35), diagnosis of age-related macular degeneration (RR=1.42; 95% CI, 1.13-1.77) and an increased intraocular pressure (>22 mm Hg in the worse eye) (RR=1.23; 95% CI, 1.06-1.42). On the basis of our multivariable model, diagnosis, sex, and recommended glaucoma medications were significantly associated with follow-up adherence. Conclusions: This study demonstrates that individuals living in underserved urban communities would take advantage of free eye exams in community sites and return for follow-up eye exams in these same settings. Future studies could investigate interventions to improve eye exam appointment adherence in community-based settings to detect glaucoma-eye conditions.